Analisis Pendidikan Karakter Berbasis Kearifan Lokal Di Sekolah Dasar - Harina Sangadji (Peneliti.net, 2023)
Integration of local wisdom in the form of the development of local food materials and the introduction of cultures in North Maluku in the Cross-Cultural Education course can be an interesting alternative for learning. This research aims to describe the implementation of a character education model based on local cultural wisdom. For example, this research uses a descriptive qualitative method to explore naturally occurring phenomena. The subjects of this study were seventh-semester students of Elementary School Teacher Education (PGSD) at STKIP Kie Raha, class of 2019. Data were obtained through observations and interviews with 15 respondents, including students, lecturers, and the Head of the PGSD Study Program at STKIP Kie Raha. The findings indicate that Cross-Cultural Education can enhance students' knowledge and skills beyond the field of education. Specifically, students responded enthusiastically to the Cirebon culture presented in Cross-Cultural Education. It can be concluded that Cross-Cultural Education based on local wisdom is able to sharpen the skills of PGSD students at STKIP Kie Raha, enabling them to have affective and psychomotor abilities alongside cognitive abilities. Thus, students are prepared to have holistic abilities that are ready to face new life challenges